Pentingnya Pendidikan Karakter dalam Bimbingan Konseling Islam - Ajeng Okvita Larasati (Journal of Theory and Practice in Islamic Guidance and Counseling, 2024)
Islamic counseling is one of the providers of education, especially in character education. Character education is needed primarily to help students understand themselves. Development of education related to counseling guidance. This research aims to determine the importance of character education in Islamic Counseling Guidance, in this case both educators and teaching staff can apply it either in the classroom or through providing examples directly to students. Seeing the complexity of the problems that occur, character education should be developed in the context of an Islamic guidance and counseling approach because it will have a good impact. Character development through guidance and counseling services is a process that shapes a student's character so that they become independent individuals. This research uses qualitative methods with a literature review. The results of this research are the importance of embedding character education in Islamic counseling not only in the classroom but also outside the classroom. Character education has an important role in moral formation. Character education according to the Islamic view is a conscious effort made by educators towards students to form students who teach and form morals, ethics, as well as a sense of good culture and noble morals that grow students' abilities.